2017
DOI: 10.1021/acs.jpca.6b12125
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Methane Combustion, Part I: Thermal Rate Constants for Hydrogen-Abstraction Reaction of CH4 + O(3P)

Abstract: The mechanism and kinetics of gas-phase hydrogen-abstraction by the O(P) from methane are investigated using ab initio calculations and dynamical methods. Not only are the electronic structure properties including the optimized geometries, relative energies, and vibrational frequencies of all the stationary points obtained from state-averaged complete active space self-consistent field calculations, but also the single-point energies for all points on the intrinsic reaction coordinate are evaluated using the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Since 2017, a series of studies on the stationary points of the ground state and the first electronic excited state for the O­( 3 P) + CH 4 → OH + CH 3 reaction have been carried out by our group using the internally contracted multireference configuration interaction (icMRCI) method. Specifically, more than two saddle points along the reaction path and several key kinetic properties including thermal rate constants are described accurately. , Our work has found that when the oxygen atom O­( 3 P) attacks the hydrogen atom with C 2 v symmetry along the CH bond direction, one 2p orbital forms a σ bond with H atom, while the other two 2p orbitals remain degenerate. When the OHC bond angle deviates from the linear shape, the Jahn–Teller conical intersection point related to the electronic state of 3 E appears between the two lowest surfaces. , According to reported literature, ,,, there are some obvious differences in the configurations of the reaction transition state, the barrier heights, and the corresponding virtual frequencies.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Since 2017, a series of studies on the stationary points of the ground state and the first electronic excited state for the O­( 3 P) + CH 4 → OH + CH 3 reaction have been carried out by our group using the internally contracted multireference configuration interaction (icMRCI) method. Specifically, more than two saddle points along the reaction path and several key kinetic properties including thermal rate constants are described accurately. , Our work has found that when the oxygen atom O­( 3 P) attacks the hydrogen atom with C 2 v symmetry along the CH bond direction, one 2p orbital forms a σ bond with H atom, while the other two 2p orbitals remain degenerate. When the OHC bond angle deviates from the linear shape, the Jahn–Teller conical intersection point related to the electronic state of 3 E appears between the two lowest surfaces. , According to reported literature, ,,, there are some obvious differences in the configurations of the reaction transition state, the barrier heights, and the corresponding virtual frequencies.…”
Section: Introductionmentioning
confidence: 86%
“…The SA-CASSCF method, with the above basis set and full valence active space, has achieved good calculation accuracy and results for this reaction system. 25,26 Further correlations such as the icMRCI method with the same basis set and active space has far exceeded the current computer capacity.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, gas phase analysis during methane combustion also shows this mechanism transition 31 which was corroborated by numerical analysis. 32 The transition as temperature was increased beyond 600 C was attributed to the mass transport as being the limiting step at such accelerated reaction rates. The fact that BIN20J remains linear could be due to it being a heavier hydrocarbon (i.e.…”
Section: Chemical Equilibrium Analysismentioning
confidence: 99%